2020
DOI: 10.18549/pharmpract.2020.4.2080
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of occupational violence towards pharmacists at practice settings in Nigeria

Abstract: Background: Occupational Violence is prevalent among healthcare workers, including pharmacists, and poses a big threat to their job satisfaction, safety, and social wellbeing. Objective: This study seeks to assess the incidents and factors associated with occupational violence towards pharmacists in Nigeria. Methods: A cross-sectional study was conducted among pharmacists practicing in Nigeria, using an online survey (Google FormTM). Occupational violence was assessed using a validated questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
2
4
0
Order By: Relevance
“…There are studies showing that women are more prone to violence [1], but data is inconsistent [15]. Another hypothesis that was confirmed and aligned with other studies from Ireland, the UK, Australia, Nigeria, and Egypt was that the patients/clients are recognized as the most common perpetrators of violence [16][17][18][19][20][21]. This was confirmed for all three types of violence and in all four included countries from the SEE region in the study.…”
Section: Pharmacy Staff Sense Of Safetysupporting
confidence: 81%
See 1 more Smart Citation
“…There are studies showing that women are more prone to violence [1], but data is inconsistent [15]. Another hypothesis that was confirmed and aligned with other studies from Ireland, the UK, Australia, Nigeria, and Egypt was that the patients/clients are recognized as the most common perpetrators of violence [16][17][18][19][20][21]. This was confirmed for all three types of violence and in all four included countries from the SEE region in the study.…”
Section: Pharmacy Staff Sense Of Safetysupporting
confidence: 81%
“…Another hypothesis that the victims of violence would talk about it mostly with their work colleagues was confirmed, as studies have shown previously in Australia, Nigeria, and Europe [17,20,23]. An especially important finding was that the number of reports to supervisors was low, probably because the previous experience has shown that in more than 90% of cases, there was no structured support for victims of violence, even in traumatic WPV, such as robberies, which confirmed another study hypothesis.…”
Section: Ethical Considerations Regarding Reporting Sexual Violence A...supporting
confidence: 78%
“…The psychiatrists and other mental health specialists are mainly available at tertiary healthcare centers to review and treat complex cases. Nigeria with over 190 million population [ 5 ], have fewer than 300 psychiatrist accounting for a ratio of about 700,000 of the population per psychiatrist (1; 700,000), most of whom are urban based, and in view of poor knowledge of mental disorders at the primary health-care level, caring for people with mental illness is typically left to family members [ 6 ]. Furthermore, nine out of every ten doctors in Nigeria are seeking to leave the country and only eight neuropsychiatric hospitals are available in the entire country responsible for professional training of psychiatric doctors as well as managing patients with psychiatric disorders [ 7 ].…”
Section: Workforce Policy and Legislationmentioning
confidence: 99%
“… 33 It is worthy that occupational violence towards pharmacists is very common in Nigerian hospitals, commonly starting verbally at the initial stage and escalating to more severe forms of abuse, as reported by Khalid et al . 34 Such hostile environment can negatively impact job satisfaction with working facility. One contributing factor could be the significant low pharmacist-to-patient ratio in public hospitals in Nigeria, leading to prolonged patient waiting times in the pharmacy unit and ensuing dissatisfaction.…”
Section: Discusionmentioning
confidence: 99%